Travel behaviour among inbound medical tourists in Kuala Lumpur - Musa, G.; Thirumoorthy, T.; Doshi, D. (Taylor & Francis (Routledge), 2012)
Despite recording the highest growth among tourism sub-sectors [Dhesi, D. (2009, March 25). Medical tourism rises in Malaysia despite economic downturn. The Star Online. Retrieved from http://www.malaysiahealthcare.com/; Leonard, T. (2009, July 24). Medical tourists to bring in RM 540 million by 2010. Retrieved from http:// www.malaysiahealthcare.com/; Tourism Malaysia. (2008). Profile of tourist by selected markets 2008. Kuala Lumpur: Tourism Malaysia], little is known empirically with regard to travel behaviour among inbound medical tourists in Malaysia. This study examined the demographic profile, travel motivation, healthcare consumption, and expenditure behaviour among them in Kuala Lumpur. Using the combination of purposeful and convenience sampling, a total of 138 questionnaires were completed, returned, and analysed. The majority of the respondents were female, middle aged, travelling with two others and Indonesians. Their main travel motivation factors were ‘value for money’, ‘excellent medical services’, ‘supporting services’, ‘cultural similarity’, and ‘religious factor’ in descending order of importance. Medical treatment, cosmetic procedure, surgical procedure, and medical check-up were important healthcare services sought after by the respondents. On average, medical tourists spent MYR 26,844.19 per visit, with females and tourists of European descent contributing significantly more. Tourists from ASEAN had stronger motivation of ‘cultural similarity’ compared with other tourists. This paper is unique in providing the empirical evidence of the city’s unique selling points (pull factors) in attracting inbound medical tourists. It also highlights the potential economic contribution and some managerial implications in terms of marketing and product development.